A STUDY ON CHALLENGES AND OPPORTUNITIES OF WOMEN FISH VENDORS IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
One of the earliest economic occupations of the human race is fishing. It follows farming in importance. Across the years, millions of women have profitably traded fish all across the world. In addition to fishing, women also contribute significantly to other fishery-related tasks. Women in the fishing industry are not represented during fisheries planning, in landing-related planning, or in mainstream fisheries planning because they are categorised as working in the postharvest sector. The socioeconomic position of the fishermen's families has a significant impact on the role of women who sell seafood. The main aim of this paper is to analyse the socio economic factors of women fish vendors and Challenges and opportunities faced by women fish vendors in the Kanyakumari District. By using convenient sampling method, 150 women respondents have been selected from Agastheswaram and Killiyoor area. Primary data is collected via well-structured questionnaire, it consists of three parts like socio economic factors of respondents, Challenges faced by Women fish vendors and opportunities of women fish vendor in the Kanyakumari District. The result of this study showed that there is a significant relationship between monthly income and Challenges of Women fish vendors and year of experience and Opportunities of Women fish vendors in Kanyakumari District